Innovations in Education, or How to Separate the Wheat from the Chaff? - M. V. Kochetkov (Высшее образование в России)
The article focuses on the criteria of pedagogical innovation. Along with such criteria as an obvious novelty and effectiveness, the author dwells on the adequacy of the considered pedagogical experience to ensure the advanced scientific and technological challenges of the time, as well as the solution of priority social problems. This implies that the tasks are reflected primarily in the conceptual documents of the country’s development. This criterion corresponds to a narrow understanding of innovation, which is associated with the system of «scientific novelty – technological (social) project – development – implementation». The broad understanding of the category «innovation» is determined by the development and preservation of the anthropological potential of society and education in particular. The relevance of the proposed basic criterion is revealed as a result of a critical analysis of a scientific publication devoted to the pedagogical experience within the system of military education. The article justifies the real anti-innovative systemic effects of the so called «Innovative approach». In the context of the growing pace of the scientific and technological revolution, the concept of «Asymmetric response» to the innovative challenges of the time is introduced. As a result of the analysis of the achievements of domestic and foreign scientists, a set of «Asymmetric measures» is proposed. They stemmed from the development of universal basic information, creative competencies, and polytechnic skills, as well as humanitarian and economic orientation of training, the development of primarily STEM-areas in school education, simulation and distance learning tools, innovative pedagogical technologies.